2004
DOI: 10.1080/0032472032000175437
|View full text |Cite
|
Sign up to set email alerts
|

Association of late childbearing with healthy longevity among the oldest-old in China

Abstract: Statistical analysis of a large and unique longitudinal data set demonstrates that late childbearing after age 35 or 40 is significantly associated with survival and healthy survival among very old Chinese women and men. The association is stronger in oldest-old women than men. The estimates are adjusted for a variety of confounding factors of demographic characteristics, family support, social connections, health practices, and health conditions. Further analysis based on an extension of the Fixed Attribute D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 43 publications
4
59
2
Order By: Relevance
“…However, a higher age at last birth was associated with better cognitive functioning in mothers. This finding is consistent with some of the few previous studies which have examined this in women (Heys et al, 2011;Ryan et al, 2009) and with results on age at last motherhood and later physical health (Yi & Vaupel, 2004). Women having children later in life may benefit from social interactions with relatively young children or they may have had a higher cognitive level initially.…”
Section: Discussionsupporting
confidence: 81%
“…However, a higher age at last birth was associated with better cognitive functioning in mothers. This finding is consistent with some of the few previous studies which have examined this in women (Heys et al, 2011;Ryan et al, 2009) and with results on age at last motherhood and later physical health (Yi & Vaupel, 2004). Women having children later in life may benefit from social interactions with relatively young children or they may have had a higher cognitive level initially.…”
Section: Discussionsupporting
confidence: 81%
“…Some studies in Sardinia on the relation between the age of women and the birth of their children and the risk associated with maternity at an advanced age have shown a high spatial variability in some variables indicative of reproductive longevity (Astolfi et al 2009;Tentoni et al 2012), with an aggregation of some municipalities constituting a central area of the island characterized by reproductive longevity coinciding with that of the longevity of the population previously obtained (Caselli and Lipsi 2006;Poulain et al 2004). The relationship between longevity and fertility has been tackled in other papers and our preliminary findings confirm results that are reported elsewhere (Perls, Albert, and Fretts 1997;Doblhammer and Oeppen 2003;Doblhammer 2000;Larke and Crews 2006;Lycett, Dunbar, and Voland 2000;McArdle et al 2006;Müller et al 2002;Vinogradov 1998;Westendorp and Kirkwood 1998;Zeng and Vaupel 2004). Unlike previous studies, however, we focus on centenarians, and here lies the novelty.…”
Section: Discussionsupporting
confidence: 81%
“…In humans, a positive association between late reproduction and longevity has been reported by some investigators (Helle et al 2005;McArdle et al 2006;Müller et al 2002;Yi and Vaupel 2004). Notably, Perls and colleagues (1997) reported that late childbearing (after age 40 in an 1896 birth cohort) was associated with a 4-fold increased likelihood of exceptional longevity.…”
Section: Discussionmentioning
confidence: 92%
“…Since then, a freshly motivated field of investigators has reported mixed results in human populations, in some cases even showing a positive association between the number of offspring and longevity (reviewed by Helle et al 2005;Hurt et al 2006;Le Bourg 2007). This positive association may imply that successful reproduction, especially at advanced age, is a surrogate for increased fitness or quality of the mother (Doblhammer and Oeppen 2003;Gagnon et al 2009;Korpelainen 2000;McArdle et al 2006;Smith et al 2002;Yi and Vaupel 2004). The reported inconsistency in the relationship between reproductive measures and longevity likely results from the difficulty in untangling the complex interplay between the biological determinants and physiological consequences of successful reproduction with social factors and decisions that also determine the tempo and number of offspring.…”
Section: Introductionmentioning
confidence: 99%